2012
DOI: 10.1016/j.jcmg.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

High Platelet Reactivity on Clopidogrel Therapy Correlates With Increased Coronary Atherosclerosis and Calcification

Abstract: OBJECTIVES To evaluate the relationship between platelet reactivity and atherosclerotic burden in patients undergoing percutaneous coronary intervention (PCI) with pre-intervention volumetric intravascular ultrasound (IVUS) imaging. BACKGROUND Atherosclerosis progresses by the pathologic sequence of sub-clinical plaque rupture, thrombosis and healing. In this setting, increased platelet reactivity may lead to more extensive arterial thrombosis at the time of plaque rupture, leading to a more rapid progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…Our hypothesis is supported by the fact that 62% of our population suffered from diabetes and 52% showed moderate to severe calcification. These are established vasculopathy markers that are directly related to increased inflammation and enhanced platelet reactivity . Additionally, the presence of severely calcified lesions adversely affects optimal stent deployment, leading to under‐expansion, malapposition, and polymer damage .…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is supported by the fact that 62% of our population suffered from diabetes and 52% showed moderate to severe calcification. These are established vasculopathy markers that are directly related to increased inflammation and enhanced platelet reactivity . Additionally, the presence of severely calcified lesions adversely affects optimal stent deployment, leading to under‐expansion, malapposition, and polymer damage .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on PCI in diabetic patients have shown an increased mortality in insulin-requiring DM patients and the reported long-term mortality rates are < 30% [4][5][6]34]. No study focused on the incremental risk associated with HRPR in diabetics, while an intravascular ultrasound study documented a relationship between HRPR and coronary atherosclerotic burden [35]. The results of our study show that the assessment of platelet reactivity while on clopidogrel treatment is clinically relevant, since it allows for the identification of patients at very high risk of cardiac death.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This was also observed when intravascular ultrasound was applied in patients with CAD under clopidogrel treatment [33] or in patients with stable CAD undergoing elective PCI which might partly account for higher risk of periprocedural myocardial infarction [34]. Though, this observation may be an epiphenomenon such as the increased number of atherosclerotic lesions in patients with diabetes mellitus [35,36].…”
Section: Platelet Reactivity and Clinical Factorsmentioning
confidence: 85%